LOCKDOWN POLICY AS A CORONA DESEASE (COVID-19) MANAGEMENT EFFORTS ASKED FROM THE ENVIRONMENTAL ASPECT OF LIFE BASED ON LAW ACT NO. 32 OF 2009 CONCERNING PROTECTION AND MANAGEMENT OF ENVIRONMENT - Mukti, Abdul; Ramdhani, Muhammad Wildan (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
The government has formed the COVID-19 (Task Force) Acceleration Countermeasures Group to discuss strategies to deal with the Corona Virus outbreak. One of Covid-19's coping strategies, namely: Social restrictions in the form of Lock Down with modifications or rules that are clarified and clear in priority areas as of now, but proposals in the form of Lock Down in priority areas such as DKI are not approved by the government. Although in the end the DKI Jakarta Government issued a policy after approval from the central government through the Minister of Health in the form of Governor's Regulation Number 33 Year 2020 concerning the Implementation of Large-Scale Social Debate in Handling Corona Disease 2019 (COVID-19) in the Special Capital Province of Jakarta and Governor Decree Number 380 Year 2020 concerning the Imposition of the Implementation of Large-Scale Social Restrictions in Handling Corona Disease 2019 (COVID-19) in the Special Capital Province of Jakarta. If the lockdown is really implemented, then this effort will indirectly have an impact on the environment, because the policy will relate to space that includes all objects, power, conditions, and living things, including humans and their behavior, which affect nature itself, continuity of life, and the welfare of humans and other living things. Therefore it is necessary to examine the relationship between the lockdown policy and COVID-19 countermeasures in the perspective of the Environmental Protection and Management Law. The author intends to find a connection point between the lockdown policy by looking at the impact it has on the environment by referring to the Law Act No. 32 Of 2009 Concerning Protection And Management Of Environment.